Park House Museum: How Florida corrections preserved its story and opened its doors to the past. - WINKLER, JOE (Corrections Today)
The article focuses on the creation and significance of the Park House Museum, established by the Florida Department of Corrections to preserve and share the history of corrections in the state. Housed in a building acquired in 1985 that previously served as a women’s halfway house and later as office space, the museum presents a chronological and thematic exploration of Florida corrections from 1868 to the present. Exhibits honor influential leaders, highlight challenges such as security and reentry, and pay tribute to fallen officers, while also providing visitors with immersive experiences like a mock prison cell. The museum aims to strengthen organizational culture, support professional development, and educate both staff and the public about the evolving responsibilities and mission of correctional work.